Analisis Technology Acceptance Model pada penggunaan QRIS (Studi Kasus UMKM Madiun) - Setiawan, Hendra; Fatmala, Indra Ayu; Hanifah, Luthfi (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2025)
The Industrial Revolution 5.0 is a major phenomenon that occurs in Indonesia. The existence of this phenomenon requires people to follow the development of the current digital era. The purpose of this study is to show the Technology Acceptance Model Analysis on the use of QRIS (Case Study of Madiun MSMEs). The study was conducted using a purposive sample of Madiun city residents which resulted in 385 respondents. The methodology of this study adopts a quantitative approach using SPSS version 20. The results of this study are as follows: Perceived Usefulness, Perceived Ease of Use, and Privacy Security, which are felt to influence Behavioral Intention to Use Perceived Usefulness, Perceived Ease of Use, and Privacy Security, which are felt to simultaneously influence Behavioral Intention to Use.